ANALISIS FAKTOR PENYEBAB RENDAHNYA LITERASI SAINS DAN MATEMATIKA SERTA UPAYA PENINGKATANNYA - Leny Hidayanti; Rizka Juniarti Pratiwi; Indriyani; Aminah; Rosyananda Nur Fauziah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The scientific and mathematical literacy of Indonesian junior high school students remains at a relatively low level, as evidenced by findings from PISA and national assessment results. This situation highlights students’ limited competence in comprehending, reasoning, and applying scientific and mathematical principles in real-life contexts.This study seeks to examine the underlying factors contributing to the low literacy achievement among junior high school students and to propose potential strategies for improvement. Employing a descriptive qualitative design through a literature review approach, this research synthesizes national and international studies concerning science and mathematics literacy.The analysis reveals that students’ low literacy levels stem from various interrelated factors, including conceptual misunderstandings, the prevalence of non-contextual teaching practices, low learning motivation, inadequate laboratory resources, and the limited use of digital technology in the classroom. Efforts to enhance science and mathematics literacy should emphasize the implementation of Project-Based Learning (PjBL) and Inquiry-Based Learning models, the integration of digital tools into learning activities, and the provision of teacher professional development programs centered on scientific and numeracy literacy. Strengthening these areas is essential to cultivating 21st-century learners who demonstrate critical thinking, effective collaboration, and creative communication skills.